Revolution on assessment for student monitoring system (i-RAS) / Mohd Samsudin Abdul Hamid and Md Rasul Mohamad Noor - Abdul Hamid, Mohd Samsudin; Mohamad Noor, Md Rasul (Unit Penerbitan FKAPP, 2019)
This particular project was developed by FILIPP OBE team leads by En Md Rasul Mohamad Noor together with En Abdul Manaff Mohd Ismail and Pn Shafienaz Ismail. This project was brought forward by Team Craggy to higher level platform at KIK and IID to get recognitions. Furthermore, it was introduced because of problems occur when the number of courses and lecturer are high in order to collect and analysed Course Outcome and Program Outcome data manually. Manual application of data collection has implemented since 2010, and it was found that there is a need for a system to interpret and analyse the assessment of all courses systematically. Therefore, a comprehensive and synchronise system called Revolution on Assessment for Student Monitoring System (i-RAS) was developed to collect and analysed COPO data accurately and automatically.